2021
DOI: 10.3390/ph14080774
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Antimicrobial Peptides as Potential Antiviral Agents in Systemic Viral Infections

Abstract: Numerous studies have led to a better understanding of the mechanisms of action of viruses in systemic infections for the development of prevention strategies and very promising antiviral therapies. Viruses still remain one of the main causes of human diseases, mainly because the development of new vaccines is usually challenging and drug resistance has become an increasing concern in recent decades. Therefore, the development of potential antiviral agents remains crucial and is an unmet clinical need. One abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 132 publications
0
16
0
Order By: Relevance
“…Antimicrobial peptides (AMPs) are an important factor of the innate immune defense for both invertebrates and vertebrates, including humans [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Recently, human defensins have been shown to inhibit SARS-CoV-2 infection [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial peptides (AMPs) are an important factor of the innate immune defense for both invertebrates and vertebrates, including humans [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Recently, human defensins have been shown to inhibit SARS-CoV-2 infection [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…These antiviral peptides can work through different mechanisms, ranging from immune regulation to direct inactivation via membrane disruption [ 17 , 18 , 19 , 20 ]. Hence, natural AMPs may be engineered into new therapeutics to help control these viruses [ 11 , 12 , 21 , 22 , 23 ]. As a proof of concept, we previously demonstrated that LL-37 could be engineered to inhibit Ebola virus entry [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants have developed mechanisms to protect themselves against invading pathogens such as viruses, bacteria, fungi, nematodes and insects ( Mott et al, 2014 ; Nishad et al, 2020 ). Since they only have the innate immune response, a wide variety of peptides is expressed ( Mott et al, 2014 ; Mammari et al, 2021 ), many of which are rich in cysteines. Plant cysteine-rich peptides have been isolated from thousands of species ( Liu et al, 2017 ); they are extremely diverse with hundreds of different peptides produced by a single plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cyclotides represent a rich natural source of bioactive molecules with prospects for development as therapeutics against cancer and infectious diseases ( Mammari et al, 2021 ). Making use of the natural evolution, a huge variety of already optimized peptides can be assessed ( Lazzaro et al, 2020 ; Atanasov et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation